Quality management and its impact on promoting academics’ innovation in Malaysian higher education / Lee Fong Cheah, Ming Yu Cheng and Yee Ting Ngoo - Lee, Fong Cheah; Ming, Yu Cheng; Yee, Ting Ngoo (Universiti Teknologi MARA, 2025)
This study seeks to identify key total quality management practices that influence innovative work behaviours among academics in Malaysian higher education institutions. Data were sourced from 568 academics in 14 Malaysian public and private universities that hold self-accreditation status. The variance-based partial least squarestructural equation model was utilised for data analysis. The findings reveal that top management commitment, customer-centricity focus, effective core quality management practices in process management and quality control improvement are key total quality management practices that significantly influence the innovative work behaviour of academics. This research provides valuable insights for policymakers and university administrators to integrate the right components of total quality management practices to foster innovative work behaviours at higher education institutions. This research addresses the theoretical and empirical gaps in understanding the nexus of total quality management in Malaysian higher education from the academic behavioural perspective.